Cosmic Order and Divine Power Pseudo-Aristotle, On the Cosmos - Thom, Johan C. (SAPERE, 2014)
The treatise De mundo offers a cosmology in the Peripatetic tradition which subordinates what happens in the cosmos to the might of an omnipotent god. Thus the work is paradigmatic for the philosophical and religious concepts of the early imperial age, which offer points of contact with nascent Christianity.